Numerical modeling of coupled electromagnetic and thermal processes in the zone induction heating system for metal billets - Grytsiuk, V. Yu.; Yassin, M. A. M. (Національний технічний університет "Харківський політехнічний інститут", 2025)
For many modern manufacturing processes, induction heating provides an attractive combination of speed, consistency and control. Multi-inductor (zone) systems with continuous billets feed are the most promising, which keep the billet cross sectional average temperature equal. It allows to avoid overheating at low throughputs and reduces the number of rejected billets. Problem. With zone induction heating systems for metal billets developing it is necessary, at the design stage, to perform a quantitative analysis of the main characteristics of the electrothermal process and provide recommendations for optimal parameters and heating modes selections. Accurate calculations for induction heating systems involve considering the distribution of the magnetic field, current density, and changes of material properties throughout volume of the heated billet. The goal of the work is to develop the numerical model and analyze the coupled electromagnetic and thermal processes in zone induction heating system for metal billets to determine the optimal power ratio of the inductors and choose rational heating modes for the billets. Methodology. The spatiotemporal distribution of the electromagnetic field and temperature throughout the volume of the billet during the induction heating process is described by the system of Maxwell and Fourier equations. For numerical calculations by the finite element method, the COMSOL Multiphysics 6.1 software package was used. All three methods of heat transfer are taken into account – conduction, convection, and radiation. Multiphysics couplings use electromagnetic power dissipation as a heat sources, and the billet material properties are specified by temperature functions. The operation of the inductors’ coils is modeled using the «Multi-Turn Coil» function, which uses a homogenized model. The translational motion of the billet is modeled by using the «Translational Motion» function. Results. The numerical 3D-model of coupled electromagnetic and thermal processes in the zone induction heating system for metal billets has been developed. Modeling was carried out for the design of a four-inductor system with the nominal capacity of 5000 kg/h. Data on the spatial distribution of the electromagnetic and temperature fields in the moving heated steel billet were obtained. Originality. Three-dimensional graphs of electrical conductivity and relative magnetic permeability change inside the moving heated steel billet are presented. Results of the temperature distribution calculations along the length of the steel billet for different inductors power ratios are provided. It is shown how the change in the power distribution of the inductors affects the billet heating parameters. Practical value. Analysis of the obtained data allows to determinate the necessary inductors powers to ensure the required heating mode. The results make it possible to reduce the time and resources required for the development, optimization of the design and improvement of the technological process of zone induction heating for metal billets.

Для багатьох сучасних виробничих процесів індукційний нагрів забезпечує привабливе поєднання швидкості, узгодженості та контролю. Найбільш перспективними є багатоіндукторні (зонні) установки з безперервною подачею заготовок, що підтримують середню температуру поперечного перетину заготовки рівною. Це дозволяє уникнути перегріву за низької продуктивності та зменшити кількість бракованих заготовок. Постановка проблеми. При розробці установок індукційного зонного нагріву металевих заготовок необхідно, на етапі проєктування, виконати кількісний аналіз основних характеристик електротеплового процесу та виробити рекомендації щодо вибору раціональних параметрів та режимів нагріву. Уточнений розрахунок індукційних нагрівальних установок передбачає врахування розподілу магнітного поля, густини струму та зміни властивостей матеріалу по всьому об’єму заготовки, що нагрівається. Метою роботи є розробка чисельної моделі та аналіз взаємопов’язаних електромагнітних і теплових процесів в установці індукційного зонного нагріву металевих заготовок для подальшого визначення оптимального співвідношення потужностей індукторів та вибору раціональних режимів нагріву заготовок. Методика. Просторово-часовий розподіл електромагнітного поля та температури по об’єму заготовки в процесі індукційного нагріву описується системою рівнянь Максвелла і Фур’є. Для проведення чисельних розрахунків методом скінченних елементів використано програмний комплекс COMSOL Multiphysics 6.1. Відтворюються всі три способи теплопередачі – теплопровідністю, конвекцією і випромінюванням. Мультифізичні зв’язки використовують розсіювання електромагнітної потужності як джерела тепла, а властивості матеріалу заготовки задані функціями температури. Робота котушок індукторів моделюється із застосуванням функції «Multi-Turn Coil», яка використовує гомогенізовану модель. Поступальний рух заготовки моделюється за допомогою функції «Translational Motion». Результати. Розроблено чисельну 3D-модель взаємопов’язаних електромагнітних і теплових процесів в установці індукційного зонного нагріву металевих заготовок. Розрахунок проведено для конструкції чотириіндукторної установки номінальною продуктивністю 5000 кг/год. Отримано дані просторового розподілу електромагнітного та температурного поля в рухомій сталевій заготовці, яка нагрівається. Наукова новизна. Представлено тривимірні картини зміни електропровідності та відносної магнітної проникності всередині рухомої сталевої заготовки, що нагрівається. Наведено розрахунки розподілу температури по довжині сталевої заготовки для різних співвідношень потужностей індукторів установки зонного нагріву. Показано, як зміна розподілу потужностей індукторів впливає на показники нагріву заготовки. Практична значимість. Аналіз отриманих даних дозволяє встановити необхідні потужності індукторів, за яких забезпечується необхідний режим нагрівання. Результати дозволяють зменшити час і ресурси, необхідні для розробки, оптимізації конструкції та вдосконалення технологічного процесу індукційного зонного нагріву металевих заготовок.
Keywords: zone heating; numerical model; inductor; temperature field; temperature field; metal billet; electrical conductivity; зонний нагрів; чисельна модель; індуктор; температурне поле; метод скінченних елементів; металева заготовка; електропровідність